2016
DOI: 10.1002/jso.24290
|View full text |Cite
|
Sign up to set email alerts
|

Complete cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal peritoneal metastasis in Norway: Prognostic factors and oncologic outcome in a national patient cohort

Abstract: Long-term outcome was in line with published results, morbidity was acceptable and there was no 100-day mortality. The results reemphasize CRS-HIPEC as an important treatment option in PM-CRC, with particularly good results in patients with PCI < 12. J. Surg. Oncol. 2016;114:222-227. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 37 publications
1
57
2
Order By: Relevance
“…In 15 of the guidelines included in this review, CRS/ HIPEC was recommended in selected patients as a curative intent treatment option for PMCRC (1)(2)(3)5,7,8,10,11,(13)(14)(15)(16)(19)(20)(21), but owing to the significant risks of morbidity and mortality the Belgian and English guidelines (2,3) recommend special arrangements for consent and appropriate clinical governance, including audit. The American Society of Colon and Rectal Surgeons (ASCRS) (18) did recommend cytoreductive surgery for PMCRC, but considered the role of HIPEC as insufficiently defined.…”
Section: Crs/hipec As Treatment Option For Pmcrc?mentioning
confidence: 99%
See 3 more Smart Citations
“…In 15 of the guidelines included in this review, CRS/ HIPEC was recommended in selected patients as a curative intent treatment option for PMCRC (1)(2)(3)5,7,8,10,11,(13)(14)(15)(16)(19)(20)(21), but owing to the significant risks of morbidity and mortality the Belgian and English guidelines (2,3) recommend special arrangements for consent and appropriate clinical governance, including audit. The American Society of Colon and Rectal Surgeons (ASCRS) (18) did recommend cytoreductive surgery for PMCRC, but considered the role of HIPEC as insufficiently defined.…”
Section: Crs/hipec As Treatment Option For Pmcrc?mentioning
confidence: 99%
“…Although not based on evidence, multidisciplinary team (MDT) discussion was recommended in 15 of the 21 guidelines (1)(2)(3)(4)(5)(6)(7)(8)10,12,13,16,(18)(19)(20). In two guidelines, the required members of the MDT were listed.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A much higher PCI is in general accepted for PMP patients, as CRS-HIPEC is shown to be beneficial with higher PCI in PMP patients than in those with PM-CRC. PCI seems to be the most important predictor of survival in PM-CRC [18, 19], while PCI as a predictor in PMP is disputed. Some authors have not found correlation with survival even in peritoneal dissemination from high-grade appendiceal primaries [20], while others have found high PCI as a predictor for poorer progression-free survival (PFS) [21].…”
Section: Discussionmentioning
confidence: 99%